Health Effect of Rescue Workers After Chemical Factory Explosion Samutprakan Province, Thailand - Witoonsut, Chonnipa (Journal of Preventive Medicine Association of Thailand, 2023)
A chemical factory explosion in Bangplee district, Samutprakarn province, generated several toxic substances, especially styrene. The health effects can occur from direct substances and other pollutants from the combustion process. A rescue worker is a high-risk group in order to their work process. This study aimed to investigate the health effects, the level of styrene metabolite in urine as well as the factors associated with the level of styrene metabolite in urine. The data in terms of individual history, work history, health effects, and the level of styrene metabolite in urine were collected from the health surveillance project in disaster prevention and mitigation officer under the control of Bangplee hospital. This data were analyzed using percentage, mean, Independent t-test, Fisher’s exact test, and Pearson’s chi-squared test. The result demonstrated that most rescue workers did not have any abnormal symptoms on duty. The most abnormal symptoms were skin problems which were skin irritation and itching (26.92%). The average level of styrene metabolite (Mandelic acid plus phenylglyoxylic acid) was 57.52 mg/g creatinine which lower than the reference value for biomonitoring in chemicals risk area in Thailand and the biological exposure indices (BEIs) of ACGHI 2021. Smoking was significantly associated with the level of styrene metabolite (p < 0.05). Therefore, health education and prevention programs for rescue workers such as smoking cessation should be considered.